Bounding Causes of Effects With Mediators - Philip Dawid; Macartan Humphreys; Monica Musio (Sociological Methods & Research, 2024)
Suppose X and Y are binary exposure and outcome variables, and we have full knowledge of the distribution of Y, given application of X. We are interested in assessing whether an outcome in some case is due to the exposure. This “probability of causation” is of interest in comparative historical analysis where scholars use process tracing approaches to learn about causes of outcomes for single units by observing events along a causal path. The probability of causation is typically not identified, but bounds can be placed on it. Here, we provide a full characterization of the bounds that can be achieved in the ideal case that X and Y are connected by a causal chain of complete mediators, and we know the probabilistic structure of the full chain. Our results are largely negative. We show that, even in these very favorable conditions, the gains from positive evidence on mediators is modest.
https://doi.org/10.25384/SAGE.19304219.v2
Keywords: 300; causal pathway; causes of effects; interval bounds; mediator; probability of causation; process tracing; qualitative methods